Visual motor integration among children with Down Syndrome in community based rehabilitation centers/ Chandra Kannan K. Thanapalan and Nurul Zahirah Mohd Sa’ad - K. Thanapalan, Chandra Kannan; Mohd Sa’ad, Nurul Zahirah (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Children with Down Syndrome (DS) shows a significant delay in physical, mental, and functional skills which eventually limit their participation in academic. The majority of DS seek services from community-based rehabilitation (CBR) center in provides services including academic skills such as handwriting. Visual-motor integration (VMI) is the crucial factor that involves during handwriting, however, VMI issues often being sidelined since the common intervention in CBR centers focused on clinical symptoms of DS. Therefore, identifying the VMI performance among children with DS can improve their skills especially in academics. To identify the level of performance in VMI among children with DS. A cross-sectional study, 33 participants in CBR centers in Kuala Selangor. VMI performance was evaluated using the Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery VMI) fifth edition. A total of 30 participants (90.90%) showed that the majority of the children with DS are in the very low performance in VMI. There is no significant difference between the level of performance in VMI among children with DS with respect to chronological age and gender. Demographical data such as chronological age and gender does not influence the level of VMI performance among children with DS.